MINERAL POTENTIAL MAPPING USING GIS FOR GOLD AND COPPER MINERALIZATION IN THE SOUTHERN MOUNTAINS OF EAST JAVA, INDONESIA - , Southammavong, Daovy ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study area (40455 km2) covers the Southern Mountains Zone of East Java, Indonesia. This zone is known as mineral districts, the distribution of 75 Au- Cu occurrences in this area was examined in terms of spatial association with various geological phenomena. Analysis of these relationships, using GIS and weights of evidence method, has predicted areas of high mineral potential. The weights of evidence method is a probability based technique for mapping mineral potential using the spatial distribution of known mineral occurrences. Mineral potential maps predicting the distribution of Au-Cu occurrences were generated from six evidence maps that consist of NE-SW lineaments, NW-SE lineaments, host rocks, heat sources, clay alteration and limonitic alteration. The result of Au-Cu potential map indicates that about 6472 km2 (16%) of the study area as favourable zones. It predicts correctly 54 (96%) of the 56 model deposits and predicts correctly 18 (95%) of the 19 validation deposits, has two main prospective target areas for future exploration are located in southwest of research areas like Pacitan, Trenggalek, Ponologo and Wonogiri Regency and located in southeast of research areas as Banyuwangi and southeast of Jember Regency. The potential areas of Au-Cu occurrences in research area is associated with NE-SW structure/lineaments, dominated surrounding the Tertiary intrusive rock unit and hosted in Miocene to Oligocene lithology rock unit. Keywords: GIS, weight of evidence method, mineral potential mapping, Southern Mountains, East Java.